Unveiling Character Education Practices: A Case Study of SMP IT Nur Hasan - Dewi Mariastuti Khasanah; Sigit Haryanto; Djalal Fuadi (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This study examines the impact of character education programs at SMP IT Nur Hasan on the formation of religious character and student independence. The purpose of this study is to evaluate the effectiveness of programs such as "Sekolahku Hijau Sekolahku Sehat", "Clean Today", "Dhuha Time", extracurricular programs, and congregational prayer. The method used was a qualitative approach with a case study design, involving in-depth interviews, participatory observation, and document analysis. The results show that the programs significantly strengthen students' moral values, religiosity, and independence, in accordance with existing character education theories. The implications of the findings include important contributions to the development of character education theory and provide practical guidance for the implementation of effective character education programs in boarding schools. This study also identifies methodological limitations that can be addressed in future research to deepen the understanding of character education in boarding schools.